Effect of denaverine hydrochloride application to heifers on the APGAR score and lactate concentration in newborn calves - Lange, Katrin; Heuwieser, Wolfgang; Fischer-Tenhagen, Carola (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2018)
Objective: The aim of this study was to evaluate the influence of Denaverine hydrochloride (DNH) in heifers on calf vitality. Material and methods: A total of 83 calvings with 38 female and 45 male calves were included in the study. Thirty minutes after onset of stage 2 of calving, 400 mg DNH or placebo (0.9% NaCl) were administered subcutaneously. If the calving procedure was not completed after 60 minutes, an extraction was conducted and pulling force was measured by using a digital force gauge. Directly after parturition, vitality of calves was evaluated using a modified APGAR score. Additionally, lactate concentration in blood from Vena auricularis was measured with a handheld measuring device (lactate scout). Results: No effect of treatment was observed on APGAR score and lactate concentration. Clinical relevance: Denaverine hydrochloride is a regularly used substance in obstetrics in veterinary medicine in many European countries. We could not confirm our hypotheses that treating heifers with DNH has a positive effect on calf vitality evaluated by APGAR score and lactate concentration in blood.
Keywords: Cattle; calving; lactate; vitality